Binding and cleavage of pro-urokinase by a tegument extract of Fasciola hepatica newly excysted juveniles activate the host fibrinolytic system - Judit Serrat; María Torres-Valle; Carolina De Marco Verissimo; Mar Siles-Lucas; Javier González-Miguel (Veterinary Research)
Abstract Plasmin, the final product of fibrinolysis, is a broad-spectrum serine protease that degrades extracellular matrix (ECM) components, a function exploited by multiple pathogens for dissemination purposes. The trematode Fasciola hepatica is the leading cause of fasciolosis, a major disease of livestock and an emerging zoonosis in humans. Infection success depends on the ability of F. hepatica newly excysted juveniles (FhNEJ) to penetrate the host intestinal wall, a process that remains incompletely understood. We have previously shown that FhNEJ are capable of binding plasminogen (PLG), the zymogen of plasmin, on their tegument surface, which leads to plasmin generation in the presence of host-derived PLG activators and subsequent degradation of laminin, a major component of the intestinal ECM. Here, we describe the interaction between a tegument extract of FhNEJ and the precursor of the urokinase-type PLG activator (pro-u-PA). We found that F. hepatica cathepsins B3, L3, enolase and glutathione S-transferase mediate this interaction, suggesting a multifactorial or moonlighting role for these proteins. Additionally, our results revealed that the tegument of FhNEJ contains a protease that is capable of cleaving and activating pro-u-PA into its catalytically active form, which positively impacts the capacity of the parasites to generate plasmin from the host PLG. Collectively, our findings indicate that FhNEJ interact with the host fibrinolytic system at multiple levels, reinforcing the potential of targeting this interaction as a strategy to prevent FhNEJ trans-intestinal migration and infection success.